2016
DOI: 10.4081/aiua.2016.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Lymphoepithelioma-like carcinoma of the bladder: A case report.

Abstract: Lymphoepithelioma is a rare histological type of low differentiated carcinoma of the nasopharyngeal region characterized by marked infiltration of lymphocytes in the area involved by tumor. However, carcinomas with this peculiar morphologic feature have been also described in various anatomic locations and they are generally designated «lymphoepithelioma-like carcinomas». Those of the urinary bladder are uncommon as they account of 0.4%-1.3% of all bladder carcinomas. They may coexist with the conventional uro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In the present case, surgery was not an option due to the patient's advanced age and personal preferences. LELCs generally have a more favourable prognosis than conventional urothelial carcinomas of the bladder; also, the prognosis has been reported to be significantly better for the pure/predominant as compared to the focal type [14,15]. Nonetheless, Tamas et al found no difference in the prognosis between pure and mixed LELCs treated by cystectomy, reporting a five-year recurrence-free risk of 59% (62% and 57%, for pure and mixed LELCs, respectively) [6].…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, surgery was not an option due to the patient's advanced age and personal preferences. LELCs generally have a more favourable prognosis than conventional urothelial carcinomas of the bladder; also, the prognosis has been reported to be significantly better for the pure/predominant as compared to the focal type [14,15]. Nonetheless, Tamas et al found no difference in the prognosis between pure and mixed LELCs treated by cystectomy, reporting a five-year recurrence-free risk of 59% (62% and 57%, for pure and mixed LELCs, respectively) [6].…”
Section: Discussionmentioning
confidence: 99%